2013
DOI: 10.2298/vsp1309836m
|View full text |Cite
|
Sign up to set email alerts
|

Distal tibial pilon fractures (AO/OTA type B, and C) treated with the external skeletal and minimal internal fixation method

Abstract: External skeletal fixation and minimal internal fixation of distal tibial pilon fractures is a good method for treating all types of inta-articular pilon fractures. In fractures types B and C dynamic external skeletal fixation allows early mobility in the ankle joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
(35 reference statements)
0
5
0
1
Order By: Relevance
“…3 Typically, remarkable comminution and impaction of the joint surface is associated with these high-energy traumas. [4][5][6] A case series of primary ankle arthrodesis using a retrograde calcaneal nail to treat closed comminuted tibial pilon fractures is presented. Clinical and radiologic outcomes as well as complications were analyzed.…”
mentioning
confidence: 99%
“…3 Typically, remarkable comminution and impaction of the joint surface is associated with these high-energy traumas. [4][5][6] A case series of primary ankle arthrodesis using a retrograde calcaneal nail to treat closed comminuted tibial pilon fractures is presented. Clinical and radiologic outcomes as well as complications were analyzed.…”
mentioning
confidence: 99%
“…Previous studies indicate that is the mean age of patients who experience that injury. 21,22 Overall, those findings were not surprising given that previous studies have demonstrated that age is associated with diminished outcomes after ORIF of ankle fractures. Dean and colleagues 23 retrospectively evaluated all patients 18 yr or older who presented for operative management of an ankle fracture over a 12-year period.…”
Section: Discussionmentioning
confidence: 81%
“…17. In addition to its functional results being equivalent to those derived from ORIF and traditional external fixation, good results were also found with the Ilizarov-type circular external fixator method combined with minimally invasive surgery. 11 The study by Milenkoviü et al 35 aimed to estimate efficacy of distal tibial pilon fractures treatment using the external skeletal and minimal internal fixation method. This retrospective study involved 31 patients with tibial pilon fractures operated on using the method of external skeletal fixation with a minimal internal fixation.…”
Section: Types Of Surgery With Internal Fixator (Orif) External and H...mentioning
confidence: 99%